PATH-20. SPATIAL MAPPING OF THERAPY-INDUCED, PATHOLOGICAL CHANGES IN GLIOBLASTOMA AT SINGLE-CELL RESOLUTION. (12th November 2021) - Vanmechelen, Maxime; Beckervordersandforth, Jan; Pey, Jon; Antoranz, Asier; Nasari, Pouya; Pantano, daniele; Bevers, Sien; Leunissen, Daphne; Moors, Wout; Messiaen, Julie; Sebastian, Ivey; Milli, Giorgia; et al.
Abstract: Glioblastoma (GBM) remains a highly malignant, intrinsically resistant and inevitably recurring brain tumor with dismal prognosis. The aggressiveness and lack of effective GBM treatments can be attributed to the highly heterogeneous and plastic nature of GBM tumor cells, which easily confer resistance to standard-of-care (SOC) therapy. While tumor progression has also been attributed to interactions with the tumor microenvironment, quantitative data describing these interactions are still largely missing. Here, we used high-dimensional, multiplexed immunohistochemistry to map evolutions in the spatial, single-cell tissue architecture of 120 paired adult GBM tumor samples derived from 60 patients at diagnosis (ND) and upon recurrence (REC) following SOC treatment. We mapped the spatial distribution of a multitude of GBM tumoral subtypes across this multicentric cohort, through which we identified a high level of heterogeneity defined by specific tumoral niches within and across patients and which evolved when subjected to SOC therapy. In addition, we describe the relationship of the various tumoral niches with their local immune-infiltrates, highlighting an even more immunosuppressive environment following SOC resistance. Finally, by aligning these findings to the observed genomic aberrations and the clinical data of the patients, we are now able to more precisely describe the heterogeneous landscape of glioblastoma and how it evolves under SOC treatment at spatial, single-cell resolution.